Faktor pencetus tonsilitis pada anak usia 5-6 tahun di wilayah kerja puskesmas bayat kabupaten klaten - Sari, Layla Tunjung, Yuli Kusumawati, SKM., M.Kes (Epid), Ambarwati, S.Pd.,M.Si (2014)
Tonsillitis caused by streptococcus infection or virus which acute or chronic nature. Tonsillitis often occurs to children 2 to 3 old years and often rise in children age also year. Children often consume is like fried food, spicy food, and also cold drink and hygiene the mouth can be exposed. The research uses case control. The subject of research is 40 children aged 5-6 years old and went on a check in primary health service of Bayat Klaten divided into 2 groups. 20 respectively as case group and 20 as group control. Instrument research use questionnaire habits fried food, spicy food , and also beverage cold and hygiene of mouth. Instrument data analysis use test chi square. The results of the study known of the habit of eating fried food, drinking of cold drink, hygiene mouth associated with an tonsillitis incidence with p-value <0,05. Another factor spicy food and habits eats snacks not correlation with tonsillitis incidence for children 5-6 years old with p-value > 0.05.